2016
DOI: 10.1016/j.molmet.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming through fatty acid transport protein 1 (FATP1) regulates macrophage inflammatory potential and adipose inflammation

Abstract: ObjectiveA novel approach to regulate obesity-associated adipose inflammation may be through metabolic reprogramming of macrophages (MΦs). Broadly speaking, MΦs dependent on glucose are pro-inflammatory, classically activated MΦs (CAM), which contribute to adipose inflammation and insulin resistance. In contrast, MΦs that primarily metabolize fatty acids are alternatively activated MΦs (AAM) and maintain tissue insulin sensitivity. In actuality, there is much flexibility and overlap in the CAM-AAM spectrum in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 96 publications
9
101
0
Order By: Relevance
“…While most work has focused on the former characteristics, little work has been conducted on understanding the metabolic phenotype of MΦs, or how MΦ metabolic phenotype influences disease progression, until recent years [6, 7]. In general, in vitro studies have shown that pro-inflammatory classically activated MΦs (LPS and IFNγ- stimulated, CAM or M1-like) are highly glycolytic while immunoregulatory alternatively activated MΦs (IL4-stimulated, AAM or M2-like) primarily oxidize fatty acids [8, 9]. However, in vivo MΦ phenotype is highly dynamic, with mixed inflammatory and metabolic phenotypes [7, 1013].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While most work has focused on the former characteristics, little work has been conducted on understanding the metabolic phenotype of MΦs, or how MΦ metabolic phenotype influences disease progression, until recent years [6, 7]. In general, in vitro studies have shown that pro-inflammatory classically activated MΦs (LPS and IFNγ- stimulated, CAM or M1-like) are highly glycolytic while immunoregulatory alternatively activated MΦs (IL4-stimulated, AAM or M2-like) primarily oxidize fatty acids [8, 9]. However, in vivo MΦ phenotype is highly dynamic, with mixed inflammatory and metabolic phenotypes [7, 1013].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid transport protein 1 (FATP1, Slc27a1 ) is an acyl-CoA synthetase wherein expression within hematopoietic populations is limited to MΦs and plasmacytoid dendritic cells [14], but not other cells that may contribute to inflammation in atherosclerosis, including monocytes, microglia, B cells, T cells, neutrophils and eosinophils [9]. We have recently reported through loss and gain of function models that FATP1 is necessary to maintain the immunoregulatory AAM phenotype in vivo and ex vivo .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations